The Mediating Role of Financial Behavior on Financial Well-being Among Small-scale Fishers in Trenggalek Regency, East Java, Indonesia - Utami, Tiwi Nurjannati; Susilo, Edi; Indrayani, Erlinda; Abidin, Zainal; Illahi, Rhochmad Wahyu (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abstract Highlight Research Financial Well-being is the result of the interaction between cognitive factors (literacy), psychological factors (attitude, self-efficacy), and behavior, but, it is closely associated with the psychological domain. Strengthening financial literacy programs by combining practical (skills and behavior) and attitudinal (attitude toward money) components to improve FSE, which in turn enhances the FWB of fishermen in Karanggongso Coast. This research expands the financial adaptation paradox to coastal fishing communities, highlighting the unique determinants, such as cognitive, psychological, and behavioral factors that shape their financial outcomes in their pursuit of FWB. Future studies should incorporate non-financial behavior mediating variables and use financial well-being measurements that consider psychological and financial aspects to test direct and indirect pathways.   Abstract Karanggongso Coast is one of the significant hubs for capture fisheries, which serves as a buffer zone in Trenggalek, Indonesia. There is more small-scale fishing, focusing on a dual livelihood system created by its location as a favorite tourist destination. Nevertheless, the community contends with persistent financial instability, characterized by income-expenditure imbalances and vulnerability to external shocks. The study aims to analyze the relationships between financial literacy, financial self-efficacy, and financial attitude on financial well-being, with financial behavior as a mediating variable among fishers in Trenggalek Regency, East Java, Indonesia. This study used Structural Equation Modelling (SEM) – Partialy Least Square (PLS) to test the relationships between financial literacy, financial self-efficacy, and financial attitude on financial well-being, with financial behavior as a mediating variable. This research was conducted from August to December 2024. The results indicate that directly the variables FL and FSE have a significant positive effect on FWB; but FSE and FA have a significant negative effect on FB, and FL has no effect on FB. Meanwhile, the variable FB has a significant negative effect on FWB. Then it is known that FB does not mediate the relationship between these factors on FWB. Thus, this study recommends strengthening financial literacy programs by combining practical and attitudinal (attitude toward financial) components to improve financial self-efficacy, which in turn enhances financial well-being. Future research should include non-financial behavioral intervening variables, such as socio-cultural, and use of financial well-being measures that consider both psychological and financial aspects.